Do relative clauses in early English have their own word order patterns? - Suárez-gómez, Cristina (Estudios Ingleses de la Universidad Complutense, 2009)
It is generally acknowledged that word-order patterns in earlier stages of the English language are more variable than those of Present-Day English. Two main word-orders compete in early English, namely VO and OV, which follow some principles in their distribution in the language. These two word-orders correlate with the degree of subordination of the clause, VO being associated with nonsubordinate clauses and OV with subordinate ones. More recently, it has been observed that the above correlation does not match with the existing data and demonstrated that there are other linguistic factors intervening in the non-random distribution of word-order patterns, as is the case of the presence of object pronominal items or negative constituents. Regarding relative clauses in early English, word-order has been generally associated with the relativizer used to introduce the relative clause, ultimately linked to the status of the clause, with relative clauses introduced by a pronominal item showing a tendency for VO and those introduced by an indeclinable relativizer for OV. The aim of this paper is to show an alternative explanation to account for word-order patterns in relative clauses in early English, and illustrate how the word-order patterns of these clauses in particular are more influenced by the type of relative clause, whether restrictive or non-restrictive, than by the word used to introduce the relative clause.